Liposuction - Dhami, Lakshyajit D. (Indian Journal of Plastic Surgery, 2008)
Advent of the tumescent technique in 1987 has allowed for safe contouring in ambulatory single session liposuction under regional or general anaesthesia. Safety and aesthetic issues define MegaLiposuction to be in Volume in litres of more than 10% of Body weight in Kgs. 870 cases of liposuction were performed between September 2000 and August 2008. In (65%) cases, the total volume of aspirate was greater then 5 liters. (Range: 5 to 25 liters). In 24% cases, the large volume liposuction was combined with a limited or a total block lipectomy. Regional anaesthesia with conscious sedation was preferred except where liposuction was for above the subcostal region (the Upper Trunk, Lateral Chest, Back, Gynaecomastia, Breast, Arms and Face) or when the patient so desired. Tumescent infiltration with Lactated ringer, adrenalin, triamcinalone and hyalase was made in all cases. This approach has clinically shown less tissue edema in the post operative period than when the conventional physiological saline was being used in place of Ringer Lactate. The amount injected varied from 1,000 ml to 12,500 ml depending on the size, site and area. Local anesthetic was included only to the terminal portion of the tumescent mixture while infiltrating the sub-costal regions, or when above costal region was combined with below costal region being anaesthetized with Spinal Anaesthesia. The aspirate was restricted to the unstained white / yellow fat and the amount of fat aspirated did not have any bearing to the amount of solution infiltrated. There was no major complication. Blood transfusion was given only on one occasion when the patient had been on aspirin and had also received Low Molecular weight Heparin intra-operative. The hospital stay ranged from 8 to 24 hours for liposuction as well as for liposuction with a lipectomy. Serous discharge from access sites, sero-sanguinous fluid accumulation requiring drainage were necessitated in less than 10% cases. Minor re-contouring touch ups were requested in 5% cases. Early ambulation was encouraged for mobilization of third space fluid shifts to expedite recovery and to prevent deep vein thrombosis. More than 10% patients were operated on for Liposuction of other areas, after a gap of 7 days to 6 months. Meticulous perioperative monitoring of systemic functions ensures safety in tumescent megaliposuction for the obese and rewarding results can be achieved in a single sitting.
Keywords: Obese; liposuction; megaliposuction; super-wet technique